Computer-Based Assessment: Dual-Task Outperforms Large-Screen Cancellation Task in Detecting Contralesional Omissions - Villarreal, Sanna; Linnavuo, Matti; Sepponen, Raimo; Vuori, Outi; Bonato, Mario; Jokinen, Hanna; Hietanen, Marja (Frontiers in Psychology, 2022)
Objective: Traditionally, asymmetric spatial processing (i.e., hemispatial neglect) has been assessed with paper-and-pencil tasks, but growing evidence indicates that computer-based methods are a more sensitive assessment modality. It is not known, however, whether simply converting well-established paper-and-pencil methods into a digital format is the best option. The aim of the present study was to compare sensitivity in detecting contralesional omissions of two different computer-based methods: a “digitally converted” cancellation task was compared with a computer-based Visual and Auditory dual-tasking approach, which has already proved to be very sensitive. Methods: Participants included 40 patients with chronic unilateral stroke in either the right hemisphere (RH patients, N = 20) or the left hemisphere (LH patients, N = 20) and 20 age-matched healthy controls. The cancellation task was implemented on a very large format (173 cm × 277 cm) or in a smaller (A4) paper-and-pencil version. The computer-based dual-tasks were implemented on a 15′′ monitor and required the detection of unilateral and bilateral briefly presented lateralized targets. Results: Neither version of the cancellation task was able to show spatial bias in RH patients. In contrast, in the Visual dual-task RH patients missed significantly more left-sided targets than controls in both unilateral and bilateral trials. They also missed significantly more left-sided than right-sided targets only in the bilateral trials of the Auditory dual-task. Conclusion: The dual-task setting outperforms the cancellation task approach even when the latter is implemented on a (large) screen. Attentionally demanding methods are useful for revealing mild forms of contralesional visuospatial deficits.